Efficacy and Safety of Half-Dose Gadopiclenol versus Full-Dose Gadobutrol for Contrast-enhanced Body MRI - Kuhl, Christiane; Csőszi, Tibor; Piskorski, Wojciech; Miszalski, Tomasz; Lee, Jeong-Min; Otto, Pamela M (Radiology, 2023)
Background Gadopiclenol is a macrocyclic gadolinium-based contrast agent (GBCA) with higher relaxivity compared with standard GBCAs, potentially allowing gadolinium dose reduction without decreasing efficacy. Purpose To investigate whether gadopiclenol at 0.05 mmol/kg is noninferior to gadobutrol at 0.1 mmol/kg for lesion visualization in body MRI. Materials and Methods A randomized, double-blind, crossover, phase 3 study was conducted between August 2019 and December 2020 at 33 centers in 11 countries. Adults with at least one suspected focal lesion in one of three different body regions (head and neck; breast, thorax, abdomen, or pelvis; or musculoskeletal system) underwent two contrast-enhanced MRI examinations, randomized to start with either gadopiclenol or gadobutrol. MRI examinations were read by three blinded expert readers for each respective body region. Readers rated border delineation, internal morphologic characteristics, and visual contrast enhancement. Three additional blinded readers assessed reader preference. For safety analysis, adverse events were recorded. The differences between gadopiclenol- and gadobutrol-enhanced MRI in terms of lesion visualization were analyzed with a generalized linear mixed model using a two-sided paired test. Results Among 273 participants (mean age, 57 years ± 13 [SD]; 162 women) who underwent both gadopiclenol- and gadobutrol-enhanced MRI and had at least one correlating lesion, 260 participants without major protocol deviations were analyzed for noninferiority. Gadopiclenol was noninferior to gadobutrol for all qualitative visualization parameters and for all readers (lower limit 95% CI of the difference of at least -0.10, which was above the noninferiority margin [-0.35]; < .001). For most participants (75%-83% [206-228 of 276]), readers reported no preference between gadopiclenol- and gadobutrol-enhanced images. Adverse events did not differ in frequency, intensity, type, or association with GBCA injection (12 of 288 participants receiving gadopiclenol and 16 of 290 receiving gadobutrol). Conclusion Gadopiclenol at 0.05 mmol/kg was comparable with gadobutrol at 0.1 mmol/kg for lesion evaluation at contrast-enhanced body MRI and had a similar safety profile. Clinical trial registration no. NCT03986138 Published under a CC BY 4.0 license. See also the editorial by Bashir and Thomas in this issue.